MARTUMPOL ADAT BATAK SIMALUNGUN : KAJIAN SEMIOTIK - Triolivia Nababan; Syafrial Syafrial; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The main problem studied in this study is the Batak Simalunguntraditional martumpol using semiotic studies. This research was conducted tounderstand the signs contained in the Batak Simalungun traditional martumpol. Themethod used in this study is descriptive medtode through a qualitative approach. Datacollection in this study is a listening method and a record method. The data found inthis study 12 signs then the signs are classified based on the formulation of the problem.The signs contained in the Batak Simalungun traditional martumpol include: (1) icon 2data, (2) index 3 data, and (3) symbol 7 data.Keywords: martumpol, Batak Simalungun tribe, semiotics